Foundations and Evolution of Preventive Education on death through the Philosophy - Ramos-Pla, Anabel (2020)
In this assay, we address the history of philosophical thought as the basis and cornerstone of preventive or previous education about death. In the article, conceptualises and contextualizes in the behalf of the reader about what constitutes death prevention education, not as a school setting, but as a goal in human development. This is intended to make an analysis of the different visions and the current situation both from the philosophical and pedagogical perspective.